Determinants of Public Satisfaction in Correctional Services: The Roles of Organizational Commitment, Service Quality, and Employee Performance - Yulina Eliza; Sutiyem Sutiyem; Desy Trimiyanti; Yoserizal Yoserizal (International Journal of Entrepreneurship and Business Management, 2026)
Public satisfaction is a key indicator in evaluating the quality of public services, particularly within government institutions that directly interact with the community. In the context of correctional institutions, public satisfaction reflects not only service quality but also fairness, transparency, and professionalism. This study aims to examine the influence of organizational commitment, service quality, and employee performance on public satisfaction at the Class IIA Padang Correctional Institution. This research adopts a quantitative approach using multiple linear regression analysis with SPSS version 16. The sample size was determined based on the Tabachnick and Fidell method, resulting in a minimum of 74 respondents. Data were collected through questionnaires and analyzed using classical assumption tests, t-tests, F-tests, and the coefficient of determination (R²). The results indicate that organizational commitment, service quality, and employee performance have positive and significant effects on public satisfaction, both partially and simultaneously. Service quality is identified as the most dominant factor influencing satisfaction. The coefficient of determination (R²) shows that 58.5% of the variation in public satisfaction is explained by the independent variables, while the remaining 41.5% is influenced by other factors. In conclusion, improving organizational commitment, enhancing service quality, and optimizing employee performance are essential strategies to increase public satisfaction in correctional institutions.